Diseño de una propuesta de mejora del área de captaciones de recursos de la cooperativa de ahorro y crédito Eloy Alfaro agencia Quito como factor de sostenibilidad social - Montoya Campoverde, Jeniffer Nathaly (2014)
On the last years the cooperative system had growth significantly, for this reason the next research intends to establish the factors for sustainability of social agents of the Cooperativa de Ahorro y Credito Eloy Alfaro. The proposal is supported on economics, legal and theorist studies that certified the validity of the document. Therefore the enforcement of innovator products through administrative improves, growth and publicity strategies, that optimize the agents involves quality of life, but that encourage savings culture not as a requirement for obtaining funding or access to other services, but as essentia